SUPERVISION - Rohimah Rohimah (Fakultas Agama Islam, Universitas Islam As-Syafiiyah, 2019)
The movement (leading) of action make appoint group members trying to achieve the goals in accordance with the business organization. “Leading is defined as motivating, directing and otherwise on influencing people to work hard to achieve the organization’s gools”. Institutions as well educational institusionas as oriented to the quality is focused on two customers that customers internal and external. The realize quality of institution or organization according Juran focused on tree activities are Planning, supervision and repairing known as trilogy Juran while Feiganbaum see activities organization quality can be seen fromthe improvement of management continuous improvement employees, leadership, and supervision in first-line, and supervison quality. This can be seen from the activities of leadership in guiding, communicate and decision making in accordance with the work will be made. In this case the most important is how leaders can inform duties and steps of work to do all member organizations to achieve the goal.